2013
DOI: 10.1007/s15010-013-0459-2
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET/CT findings during immune reconstitution in an HIV-1 patient infected with visceral leishmaniasis

Abstract: Visceral leishmaniasis can rarely be unmasked by immune reconstitution in human immunodeficiency virus (HIV)-1-infected patients. We report the first case of immune reconstitution associated with leishmaniasis in an HIV patient to be imaged with [(18)F]fluorodeoxyglucose positron emission tomography (FDG/PET), at both baseline and after therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…During the investigation of two cases with the fever of unknown origin, we performed PET-CT. There was an increased F-18 FDG uptake in the spleen (increased diffuse F-18 FDG uptake in the spleen both with and without superimposed hypodense nodules), similar to the patients in the literature (28,29).…”
Section: Conflict Of Interestsupporting
confidence: 82%
“…During the investigation of two cases with the fever of unknown origin, we performed PET-CT. There was an increased F-18 FDG uptake in the spleen (increased diffuse F-18 FDG uptake in the spleen both with and without superimposed hypodense nodules), similar to the patients in the literature (28,29).…”
Section: Conflict Of Interestsupporting
confidence: 82%
“…Thus, iron overload with hepatosplenomegaly detected in this study may reflect the severe conditions in the Leishmania infection and its associated HLH. Several studies have demonstrated the pattern of Fluorine-18 Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (F18 FDG-PET/CT) in the visceral leishmaniasis [27][28][29]. Diffuse splenic and bone marrow uptake of FDG is the main feature in the VL patients, and VL associated HLH cases presented more significantly elevated diffuse uptake in the liver, spleen and spinal column.…”
Section: Discussionmentioning
confidence: 99%
“…Though rK39 RDT is highly sensitive and specific, it has limited role in the disease prognosis [14]. Recently, [ 18 F] fluorodeoxyglucose positron emission computed tomography (FDG-PET/CT) imaging has been reported as a useful tool to investigate fevers of unknown origin in HIV-1 patients with VL [15].…”
Section: Introductionmentioning
confidence: 99%